The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.5935/1806-6690.20170025
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Kit of Plate-Trapped Antigen Enzyme-Linked Immunosorbent Assay for Identification of Plant Viruses

Abstract: Many methods can be used for arriving in a correct virus disease diagnose, and the serological techniques are the most used methods for plant virus identification. The indirect enzyme-linked immunosorbent assay (Indirect-ELISA) or plate-trapped antigen ELISA (PTA-ELISA) has been useful for detection of viruses in a wide range of situations, especially to test a large number of samples in a relatively short period of time. Immune-biological Companies have developed practical kits for direct ELISA or double anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…PTA-ELISA was reported to be useful for testing an adequate number of samples for the detection of viruses in a wide range of situations over a short period. A study showed the detection of various plant viruses, such as the Squash mosaic virus (SQMV), Cowpea severe mosaic virus (CPSMV), Cucumber mosaic virus (CMV), Cowpea aphid borne mosaic virus (CABMV), Zucchini yellow mosaic virus (ZYMV), and Papaya lethal yellowing virus (PLYV) in squash, cowpea, and papaya plants [ 61 ]. The detection of Tomato yellow leaf curl Thailand virus, (TYLCTHV) in tomato, pepper, eggplant, okra, and cucurbit plants was analyzed using a TAS-ELISA (triple antibody sandwich enzyme-linked immunosorbent assays) [ 62 ].…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…PTA-ELISA was reported to be useful for testing an adequate number of samples for the detection of viruses in a wide range of situations over a short period. A study showed the detection of various plant viruses, such as the Squash mosaic virus (SQMV), Cowpea severe mosaic virus (CPSMV), Cucumber mosaic virus (CMV), Cowpea aphid borne mosaic virus (CABMV), Zucchini yellow mosaic virus (ZYMV), and Papaya lethal yellowing virus (PLYV) in squash, cowpea, and papaya plants [ 61 ]. The detection of Tomato yellow leaf curl Thailand virus, (TYLCTHV) in tomato, pepper, eggplant, okra, and cucurbit plants was analyzed using a TAS-ELISA (triple antibody sandwich enzyme-linked immunosorbent assays) [ 62 ].…”
Section: Methods For Plant Viral Diagnosticmentioning
confidence: 99%
“…The ELISA indirect test has some advantages: speed of execution, low cost, and possibility of performing a large number of samples, consisting of an excellent seroepidemiological survey tool, which requires screening tests with good sensitivity (SEABRA et al, 2016;NASCIMENTO et al, 2017;KIM et al, 2019). Positive and negative predictive values indicate that the standardized test described here is capable of detecting 53.52% of positives and 58.62% of negatives, offering a good safety margin for a screening test.…”
Section: Discussionmentioning
confidence: 97%
“…Plate Trapped Antigen-ELISA (PTA-ELISA) tests from plant extracts have already been demonstrated as a stable platform for low-cost detection of virus (Mowat and Dawson, 1987;Nascimento et al, 2017). Thus, it could be used to expand access to visceral leishmaniasis diagnosis in low-income countries.…”
Section: Discussionmentioning
confidence: 99%
“…A significant concern toward PTA-ELISA is the stability of this type of test based on non-purified antigens. However, stability of up to 20 months at room temperature has been described for a PTA-ELISA for the detection of plant viruses (Nascimento et al, 2017). Another disadvantage of using total soluble proteins in a PTA-ELISA is that it can lead to a lower sensitivity as the recombinant protein is diluted into the host proteins pool (Garnsey and Cambra, 1993), and the plant compounds could interfere with the reaction.…”
Section: Discussionmentioning
confidence: 99%